Evaluation of financial performance of South African gold, platinum, coal and iron ore mining companies for the period 2012 – 2016. - Makamba, Tapiwa (My University, 2018)
South Africa hosts vast mineral resources that it has a great global comparative advantage in terms of mineral resources endowment. The mining industry continues to be a key contributor to the country’s economy. However, since the end of the 2008 global economic crisis, the industry has faced multiple global and local economic and operational challenges that together threaten the survival and sustainability of the industry. This study investigated the effects these challenges had on the financial performance and health of the South African mining industry for the period 2012 to 2016. The research focussed on the performance of platinum, gold, coal and iron ore mining companies listed on the Johannesburg Stock Exchange. To determine the companies’ financial performance, financial ratios were used to measure the profitability, liquidity, solvency, activity and market performance of the companies. Validation of the findings of ratio analysis was done using the Altman Z”-score analysis model that also classified the companies’ financial health over the period. As commodity price is a key driver of mining companies’ value, a Pearson coefficient correlation analysis was done to determine the influence commodity price had on the performance of the mining companies during the period. The study found that the overall financial performance and health of mining companies was declining over the course of the analysis period. Profitability was low for all commodity sectors except iron ore, liquidity was good for the platinum and iron ore sectors but poor for the gold and coal sectors. All commodity sectors had good activity ratios but, had poor solvency and market ratios except the iron ore sector. Only the iron ore mining sector performed well in all the ratio categories. Declining commodity prices for most commodities, increasing operating costs, declining productivity were found to be the main factors that affected the performance of mining companies. In addition, the impact on the mining sector of government and policy uncertainty such as the Mining charter, resulted in wholesale decline in the value of mining stocks as investor confidence waned. The Altman Z”-score analysis showed that most analysed companies were in a safe zone, but a few were in a distress zone during the analysis period. Because mining Page | companies are price takers, it is important that they improve on their efficiencies to remain viable and sustainable against a constrained economic and operational challenges.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Science in Engineering.
Keywords: Ratio analysis; Corporations--Valuation; Mineral industries--Economic aspects--South Africa